Design, fabrication, in vivo and in vitro characterizations of novel PLGA thread-embedding materials for juvenile pseudo-myopia. Issue 2 (1st February 2021) - Fu, Shaoju; Zhang, Peihua
Abstract: Polylactic-co-glycolic acid (PLGA) acupoint catgut-embedding (ACE) multifilament was braided into thread structure, in vivo and in vivo performances were fully investigated. These findings indicated that samples had the relatively intact structures in the first 4 weeks, and their weights lost more than 80% in the 10 weeks. With the further degradation, mechanical properties became worse, a sharp decrease was observed in the 6 weeks. Samples presented more than 75% of cells being viable, and the surrounding tissues of samples grew well according to Hematoxylin and eosin (H&E) staining measurement. In sum, these findings warrant further study on PLGA embedding materials with outstanding clinical efficacy.